2021
DOI: 10.14569/ijacsa.2021.0120941
|View full text |Cite
|
Sign up to set email alerts
|

Distance Education during the COVID-19 Pandemic: The Impact of Online Gaming Addiction on University Students’ Performance

Abstract: The COVID-19 pandemic has forced most universities worldwide to convert to distance education to ensure the educational process remains uninterrupted. The COVID-19 pandemic-related confinement orders have led students to be more engaged with online games. However, for a minority of students, excessive playing can become problematic and addictive. Few studies investigated the long-term effect of COVID-19 on game addiction among university students. The present study investigates the changes in online game addic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
0
3
1
3
Order By: Relevance
“…In contrast to our results, a different study by Samaha and Hawi found no connection between an obsession with mobile games and academic performance 21 . Amid COVID‐19 pandemic, Abou Naaj et al discovered an association between academic performance and digital games 22 . Likewise, Valdez et al figured out that students benefit from moderate online gaming 23 .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to our results, a different study by Samaha and Hawi found no connection between an obsession with mobile games and academic performance 21 . Amid COVID‐19 pandemic, Abou Naaj et al discovered an association between academic performance and digital games 22 . Likewise, Valdez et al figured out that students benefit from moderate online gaming 23 .…”
Section: Discussioncontrasting
confidence: 99%
“…21 Amid COVID-19 pandemic, Abou Naaj et al discovered an association between academic performance and digital games. 22 Likewise, Valdez et al figured out that students benefit from moderate online gaming. 23 Nonetheless, our research has shown a strong correlation between students' lower academic achievement and their long-term online gaming habit.…”
Section: Discussionmentioning
confidence: 99%
“…Nilai signifikansi ,032, jika nilai sig 0,032 < 0,1 maka terdapat korelasi atau hubungan pengawasan orang tua dengan kebutuhan istirahat dan tidur di SMP Tunas Bangsa Depok Tahun 2021. Nilai correlation coefficient ,255 maka arah hubungan penelitian ini adalah positif, Sehingga interpretasinya semakin tinggi pengawasan orang tua maka semakin tinggi kebutuhan istirahat dan tidur (Naaj, 2021).…”
Section: Hubungan Pengawasan Orangtua Dengan Kebutuhan Istirahat Dan ...unclassified
“…Bilişsel esneklik düzeyi, bireyin yüzleşmekte olduğu durum ya da olayları kontrolünün dışında olarak değerlendirmesiyle azalabilmektedir. Bu anlamda kaygı ve strese neden olabilecek koşulların algılanması ve değerlendirilmesindeki çeşitlilik, bilişsel esneklik düzeylerindeki farklılıklara temel oluşturabilmektedir (Aktepe, 2022;Gabrys, Howell, Cebulski, Anismana ve Matheson, 2019) (Currie, 2021;Gainer ve diğerleri, 2021;Geng ve diğerleri, 2021;Tambelli, Forte, Favieri ve Casagrande, 2021;Wild, McKinnon, Wilkins ve Browne, 2022), alkol/madde/tütün bağımlılıkları, davranışsal bağımlılıklar (Dubey ve diğerleri, 2020;Ekinci, Karaali, Parçali, Suner ve Satilmiş, 2021;Elsayed, 2021;Fidancı, Aksoy, Yengil Taci, Ayhan Başer ve Cankurtaran, 2021;Naaj ve Nachouki, 2021;Pirnia ve diğerleri, 2020) yeme ve uyku bozuklukları (Giel, Schurr, Zipfel, Junne ve Schag, 2021;Inönü Köseoğlu, 2021;Marvaldi, Mallet, Dubertret, Moro ve Guessoum, 2021;Phillipou ve diğerleri, 2020) dahil olmak üzere birey ve toplum ruh sağlığına birçok olumsuz etkisi olduğuna yönelik bulgular sunmaktadır.…”
Section: Sonuç Tartışma Ve öNerilerunclassified